Creating a Virtual Food Policy Expert Using Artificial Intelligence: Advantages and Disadvantages of Customized Chatbot - Koo, Jawoo (AgriLinks, 2023)
Artificial intelligence (AI) tools are rapidly transforming the way people work, providing opportunities for improving efficiency, accelerating innovations and supporting human decision-making. The area of food policy research and policymaking is no exception. In a previous blog, we argued that policymakers should not rely exclusively on AI-powered chatbots (e.g., Bard, ChatGPT, and Claude), given that the outputs of current versions of AI simply draw upon a vast number of existing passages in publications written by humans, assembled without logic and, consequently, prone to errors. In addition, many chatbots do not identify the sources used for assembling specific policy information, thus potentially undermining trust and credibility. Still, the potential of having a virtual assistant at your fingertips is so appealing that we wanted to test it ourselves.